Investigation of differences in cortical activation during wrist flexion and extension performed under real, passive and motor imagined paradigms - Stoeckigt, Stefan (Division of Biomedical Engineering, 2017)
The neuromuscular control comparison between flexion and extension of the upper extremities has been conducted in a number of studies. It has been speculated that differences in the corticospinal pathway between flexion and extension may play a role in the cortical difference detected between flexion and extension, resulting in higher cortical activation for extension. However, it is still unclear as to what roles these pathways play, and to what degree other factors (muscle force activation, sensory feedback, frequency of movement, structural and/or functional differences) might influence the cortical activation in the brain. It has been speculated that the difference in cortical muscular pathways is due to flexion movements being used more often in day to day activities, therefore requiring less cortical activation for that movement. Through the investigation of the cortical differences present during different movement types, a deeper understanding into the differences between flexion and extension may be obtained. No previous study has compared the cortical differences between flexion and extension of the upper extremities during different movement types. In this study, an offline investigation is conducted between wrist flexion and extension, during real, passive and motor imaginary movement with the help of a servo controlled hand device. Simultaneous recording of EEG, EMG and wrist dynamics (velocity, angle, strain) were made on fifteen healthy right handed subjects performing 60 randomized repartitions of right wrist flexion and extension, for kinaesthetic motor imaginary, passively moved, and voluntary real active movements. Real movements were conducted at 10% relative subject maximum voluntary contraction (MVC). A servo controlled hand device was used to regulate dynamic force applied for real movements, and provide motion during passive movements. The use of different movement types with the aid of a servo controlled hand device, may give a deeper understanding into the effects of muscle force activation, rate of movement and corticospinal pathway on flexion and extension. In order to investigate the cortical differences between flexion and extension, subjects perceived difficulty, movement dynamics, movement related cortical potential (MRCP), event related desynchronization and synchronization (ERD/ERS), and phase locking value (PLV) were measured. Each measurement examines a different aspect of the cortical activation present in the brain, during the different movement types. Although relative muscle force activation between wrist real flexion and extension was similar, the motor cortex activation during extension was higher than during flexion, by MRCP and mu-band ERD, with subjects also perceiving real wrist extension to be more difficult to perform. Passive movements found higher motor cortex activation for flexion (MRCP, beta-band ERD), however higher somatosensory cortical activation was present during extension, by mu-band ERS and PLV. Motor imagined wrist flexion showed higher cortical activation during wrist flexion, by MRCP and beta-band ERD. Although numerous variables were tested (each in difference frequency bands), with some being significant and others being non-significant, overall it can be suggested that there was higher cortical activation for extension. The higher cortical activation during wrist extension movements may be due to corticospinal and somatosensory motor control pathways to motor neuron and from sensory neuron pools for extensor/flexor muscle and muscle spindle of the upper extremities. This investigation contributes to the current literature relating to cortical differences between flexion and extension of the upper extremities, by including the real, passive and motor imaginary differences between flexion and extension.